Heavy Metals Pollution of the Soil Environment by Landfill Sites: A Case of Kieu Ky Landfill - Gia Lam - Hanoi - Ha, Hoang Ngoc (VNU Journal of Science: Earth and Environmental Sciences; Vol 34 No 2DO - 10.25073/2588-1094/vnuees.4249, 2018)
World research results indicate that untreated leachate contains high contents of heavy metals that are likely to pollute the soil and groundwater environment. Most studies have shown that soil and groundwater in the waste landfill sites and adjacent areas are not polluted by heavy metals at levels greater than those permitted for agricultural land. However, the studies have shown that waste and leachate contribute to increase of heavy metals in soil and groundwater based on the spatial analysis and on the base concentration of heavy metals in soil and groundwater. According to the results of analysis of heavy metals in soil samples at Kieu Ky landfill site, the contents of some heavy metals exceed the permitted level in Vietnam national standard QCVN 03-MT: 2015/BTNMT such as As (content 28-30g/kg) and Cr 154-294mg/kg) from 1.5 to 2 times. The distribution curves of soil heavy metals in the depth have given the depth of heavy metals transport of about 4-5m. The results also show that the level of heavy metal pollution increases as the distance to the waste landfills decreases: the Cr, Pb and Zn contents at a distance of 5 m to the edge of the landfill site are only about 50% in compare to the soil in the landfill edge. Keywords: Landfill, Solid waste, Heavy metal, Atomic Absorption (Emission) Spectrometry-AAS (AES), ICP-MS.